Analysis of Intelligent Pipeline Perception Technology Based on Terminal - Binfeng Yan; Hui Dong; Yuhua Hou (Dianxin kexue)
The background of the intelligent pipeline was briefly introduced,the multidimensional perception technology of intelligent pipeline was analyzed,the perception technology based on terminal was focused on,the corresponding solutions were put forward,that these solutions would be beneficial to realize the intelligent pipeline and finally the difficulties and challenges of these solutions were analyzed.It has carried on the beneficial exploration for the further technology research and practical deployment of the intelligent pipeline.